2012
DOI: 10.3767/003158512x658123
|View full text |Cite
|
Sign up to set email alerts
|

β-tubulin paralogue <I>tubC</I> is frequently misidentified as the <I>benA</I> gene in <I>Aspergillus</I> section <I>Nigri</I> taxonomy: primer specificity testing and taxonomic consequences

Abstract: β-tubulin (benA, tub-2) and calmodulin (caM) are crucial genes in the taxonomy of Aspergillus section Nigri. Widely used β-tubulin primers are not specific for the benA gene for some taxa and preferentially amplify the tubC paralogue. Sequences of the tubC paralogue are widely combined with benA sequences in recent taxonomical works as well as other works, resulting in incongruent trees. In this study we newly provide benA sequences for several ex-type strains, which were characterised using the tubC gene only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 52 publications
(69 reference statements)
2
38
0
4
Order By: Relevance
“…A. fijiensis ) was previously isolated from soil, Fiji (CBS 313.89), Lactuca sativa , Indonesia (CBS 119.49) (Varga et al 2011), guano, Peru (IHEM 18675), corneal scraping keratitis, India (IHEM 22812), droppings of Coenobita sp., Bahamas (IHEM 4062) (Hendricks at al . 2011), and industrial material, China (CCF 108) (Hubka & Kolarik 2012). This is the first report of A. brunneoviolaceus isolated from the indoor air environment and the first reported isolation in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A. fijiensis ) was previously isolated from soil, Fiji (CBS 313.89), Lactuca sativa , Indonesia (CBS 119.49) (Varga et al 2011), guano, Peru (IHEM 18675), corneal scraping keratitis, India (IHEM 22812), droppings of Coenobita sp., Bahamas (IHEM 4062) (Hendricks at al . 2011), and industrial material, China (CCF 108) (Hubka & Kolarik 2012). This is the first report of A. brunneoviolaceus isolated from the indoor air environment and the first reported isolation in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Initial results indicated that the BT2 primers (BT2a, BT2b) were amplifying paralogous genes. The primers (BT2f and T22) and procedures of Hubka and Kolarik [22], developed to resolve this problem in Aspergillus japonicus, were used to conduct repeated amplification and sequencing of the suspect products. This procedure also produced the paralogous gene products.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear ITS rDNA region internal transcribed spacers (ITS1 and ITS2) and 5.8S subunits were amplified with primer set ITS5/ITS4 [18]. The reaction mixtures and conventional PCR protocols were the same as in Hubka and Kolarik [19]. Custom purification of PCR amplicons and sequencing was conducted at Macrogen Inc. (Seoul, South Korea) using the same primers.…”
Section: Identification Of Pythium and Phylogenetic Analysismentioning
confidence: 99%